2016
DOI: 10.1002/hbm.23146
|View full text |Cite
|
Sign up to set email alerts
|

Combining tract‐ and atlas‐based analysis reveals microstructural abnormalities in early Tourette syndrome children

Abstract: Tourette syndrome (TS) is a neurological disorder that causes uncontrolled repetitive motor and vocal tics in children. Examining the neural basis of TS churned out different research studies that advanced our understanding of the brain pathways involved in its development. Particularly, growing evidence points to abnormalities within the fronto-striato-thalamic pathways. In this study, we combined Tract-Based Spatial Statistics (TBSS) and Atlas-based regions of interest (ROI) analysis approach, to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 68 publications
(67 reference statements)
5
38
1
Order By: Relevance
“…Furthermore, our result showed that the precuneus is also a structural hub and its structural connection with parietal regions is significantly disrupted in TS children. The previous study [Wen et al, ] also reported significantly reduced FA value or increased RD value in precuneus WM, which reveals microstructural abnormalities in this region and is in line with our finding.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Furthermore, our result showed that the precuneus is also a structural hub and its structural connection with parietal regions is significantly disrupted in TS children. The previous study [Wen et al, ] also reported significantly reduced FA value or increased RD value in precuneus WM, which reveals microstructural abnormalities in this region and is in line with our finding.…”
Section: Discussionsupporting
confidence: 93%
“…Evidence from a magnetization transfer ratio (MTR) study also showed WM reductions in the inferior frontal gyrus and cingulate gyrus in TS patients [Muller‐Vahl et al, ], and previous postmortem study [Thomas et al, ] proved MTR reductions correlate with myelin and axonal loss in the WM. So, our results showed that reduced white matter integrity is associated with TS children [Plessen et al, ; Wen et al, ] from a network perspective, and the reduced global and local efficiencies in TS group may indicate a disturbance of the normal balance in their structural brain network, which tends to have a more randomized configuration [Peng et al, ].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Philips et al, 2016b) and Tourette’s syndrome (e.g. Wen et al, 2016). It is beyond the scope of this review to discuss all brain disconnectivity in greater depth (for review on disconnection syndromes, see e.g.…”
Section: Atypical Development Of Short-range Connectivity In Humanmentioning
confidence: 99%